2019
DOI: 10.1038/s41598-019-45528-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MafA and MafB expression promotes islet inflammation

Abstract: Maf transcription factors are critical regulators of beta-cell function. We have previously shown that reduced MafA expression in human and mouse islets is associated with a pro-inflammatory gene signature. Here, we investigate if the loss of Maf transcription factors induced autoimmune processes in the pancreas. Transcriptomics analysis showed expression of pro-inflammatory as well as immune cell marker genes. However, clusters of CD4+ T and B220+ B cells were associated primarily with adult MafA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
(77 reference statements)
1
11
1
Order By: Relevance
“…In this study, we did not detect obvious immune cell infiltration in the pancreatic tissues of male A0B Δpanc mice. However—different from our results—according to Singh et al [ 37 ], loss of Mafa and Mafb expression promotes inflammation of the pancreatic islets. This may be explained by the following two reasons: First, the mice models used by Singh et al [ 37 ] were Mafa −/− and Mafb +/− mice, which were whole body knockouts, while the mice used by us were Maf −/− ; Mafb flox/flox , and Pdx1-CreER TM .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not detect obvious immune cell infiltration in the pancreatic tissues of male A0B Δpanc mice. However—different from our results—according to Singh et al [ 37 ], loss of Mafa and Mafb expression promotes inflammation of the pancreatic islets. This may be explained by the following two reasons: First, the mice models used by Singh et al [ 37 ] were Mafa −/− and Mafb +/− mice, which were whole body knockouts, while the mice used by us were Maf −/− ; Mafb flox/flox , and Pdx1-CreER TM .…”
Section: Discussioncontrasting
confidence: 99%
“…Second, the feeding time may also affect the occurrence of some histological changes. Singh et al [ 37 ] kept the mice for 6–8 months, 2-4 months longer than ours. Collectively, owing to the different genotypes and feeding times, the phenotype may be explainable.…”
Section: Discussionmentioning
confidence: 69%
“…In hepatic ischemia-reperfusion, the lack of miR-155 can upregulate SOCS-1 expression and reduce the hepatic damage [11]. Maf is a family described as transcriptional activators and MafB plays a crucial part in mediating the inflammatory reaction in immune cells [19]. e results of our study revealed that miR-155 was upregulated while MafB was downregulated in patients with CIRI and CIR cell models in vitro and mouse models in vivo.…”
Section: Discussionmentioning
confidence: 58%
“…MafB is a kind of the large musculoaponeurotic fibrosarcoma oncogene (Maf ) family proteins with a basic leucine zipper structure, which acts as a critical transcriptional activator of anti-inflammatory cytokine genes [19]. Considering information about the underlying mechanism of miR-155 in CIR injury is rarely known, we conducted this research to examine the expression of miR-155 and MafB and their relationship in patients with cerebral ischemiareperfusion injury (CIRI), exploring their biological functions and molecular mechanism in oxygen glucose deprivation/reoxygenation (OGD/R) induced SH-SY5Y cells in vitro, as well as in the mouse models with middle cerebral artery occlusion (MCAO) in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…MafA floxed (MafA fl/fl ) mice were crossed with Sox2-Cre or RIP-Cre mice to obtain total MafA [22] or β-cell-specific [23] MafA deletion. Mice were maintained on C57BL/6 background and housed in colony cages (3-5/cage) in a 12h light/dark cycle with controlled humidity and temperature and free access to standard diet and water.…”
Section: Animalsmentioning
confidence: 99%